Silk of the common clothes moth, Tineola bisselliella, a cosmopolitan pest belonging to the basal ditrysian moth line. (March 2021) - Rouhova, Lenka; Kludkiewicz, Barbara; Sehadova, Hana; Sery, Michal; Kucerova, Lucie; Konik, Peter; Zurovec, Michal
Abstract: Many lepidopteran larvae produce silk secretions to build feeding tubes and cocoons that play important protective roles in their lives. Recent research on the silk of bombycoid and pyralid moths has shown that it contains several highly abundant silk components with remarkable mechanical properties. It was also found to contain a number of other proteins of which the functions have yet to be identified. To gain an overview of the silk composition in more primitive lepidopteran species and to identify the core silk components common to most species, we analyzed the cocoon proteins of Tineola bisselliella, which belongs to the basal ditrysian moth line. Using de novo transcriptome sequencing combined with mass spectrometry (MS)-based proteomics, we detected more than 100 secretory proteins in the silk cocoons. Fibroin, sericins, and protease inhibitors were found to be the most abundant proteins, along with several novel candidate silk components. We also verified the tissue and developmental stage specificity of the silk protein expression and characterized the morphology of both the silk glands and silk in T. bisselliella . Our study provides a detailed analysis of silk in the primitive moth, expands the known set of silk-specific genes in Lepidoptera, and helps to elucidate their evolutionary relationships. Graphical abstract: Image 1 Highlights: Functional subdivision of silk glands and silk composition in a basal moth, T. bisselliella, resembles those in more advanced lepidopterans. 101 secreted proteins were detected based on peptide fingerprinting in the cocoons from T. bisselliella . 25 of the identified proteins were specific to silk and their roles are discussed. Our study broadens the currently known set of silk proteins and describes their expression and evolution.